Influence of aspect on vegetation dynamics: insights into the understory vegetation diversity of the dry temperate forests of South Waziristan Agency, Pakistan - Khan, Imran; Zahid, Din Muhammad; Zubair, Muhammad; Manzoor, Syed Amir; Yasin, Ghulam; Mohammad, Mamoona Wali; Khan, Khalid Ali; Rahman, Shafeeq Ur; Qin, Anzhen (Frontiers in Forests and Global Change, 2023)
Dry temperate forests of Pakistan exhibit rich diversity of understory floral species. These important and endemic plant species play a pivotal role in the ecosystem functioning and providing livelihoods to the forest communities. South Waziristan located in southwest of Pakistan is known for its rare pure stands of Pinus gerardiana Wallichex. D. Don forests. Due to rapidly expanding population and prevailing war-like situations are leading to deforestation and causing disturbance to the understory vegetation of this valuable forest. The current study aims to fill already scanty information present in the literature regarding the diversity status of understory vegetation in P. gerardiana forests. Data for understory vegetation diversity was gathered for the northern and southern aspects of forest. A 50 m 2 sampling plot along with the placement of 50 numbers of 1x1m 2 quadrats on both sites were laid out 2 to determine species dominance, diversity, and evenness using Simpson, Shanon, Marglef, and Buzas and Gibson indices. The study depicted 612 individuals of about 29 species representing 23 families from the study site. The most abundant species in all of the sites was Salvia Glutinosa (IV= 0.52).Southern aspect depicted the lowest diversity, but had high species dominance. Allium carolinianum DC. in this site came out to be the most important species (IV=0.74). The most abundant species were medicinal plants (75%), followed by edible plants (25%). Aspect had a significant effect on the understory vegetation and different categories of plants with respect to their diversity, dominance, evenness as predicted by various diversity indices. This study provides essential insight in to the florisitic diversity and community structure of the fragile pine nut understory vegetation in South Waziristan, which was hitherto not available. It was concluded that the southern aspect of understudy dry temperate forests depicted lower diversity and density as compared to northern aspect. But it was observed that southren aspect more specifically had more density and diversity of medicinal plants. It is therefore the need of hour that conservation of these species from grazing and unsustainable harvesting must be ensured for sustaining the livelihood of the inhabitants.